IMPLEMENTASI SISTEM INOVASI DAERAH (SIDA) PADA SCIENCE TECHNO PARK (STP) PROVINSI RIAU - Rinanda, Alfadhia; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at the Bapedalitbang Office, as well as Sience Techno Park (STP) in Riau Province. This research was conducted with the objectives of (1) to determine the implementation of the Regional Innovation System Program (SIDa) at the Science Techno Park (STP) in Riau Province. (2) To find out the inhibiting factors for the implementation of the Regional Innovation System Program (SIDa) at the Science Techno Park (STP) in Riau Province. The data collection techniques used in this study were observation, interviews, and documentation. Then the data analysis technique that the author uses in this study is descriptive quantitative. The population and sample in this study consisted of (1) the Bapedalitbang Office (2) the Sience Techno Park (STP) in Riau Province which was then sampled using the Incidental Technique. Sampling. This study shows that: The implementation of the SPALD-T development has been carried out quite well, this can be seen from several indicators, such as: 1) Ambiguity, 2) Executors at the Frontline (implementing apparatus), 3) Funding and Resources, and 4) Politics and Conflict. The ambiguity problem occurs because of the long time for planning and implementing the Regional Innovation System (SIDa) at the Science Techno Park (STP) in Riau Province, so that there have been many changes in government agencies. There are several problems that hinder the Implementation of the Regional Innovation System Program (SIDA) at Sience Techno Park (STP) In Riau Province, namely: 1) lack of experts to implement the program; 2) Not yet optimal community participation in the development of agricultural-based industrial clusters (Agro-industry); 3) weak community participation in increasing the production of raw materials, so that science techno park (STP) finds it difficult to develop a network of fish, coconut and sago-based product innovations. Keywords:    Regional Innovation System